Die westpaläarktischen Thamiocolus-Arten (Coleoptera: Curculionidae). - Dieckmann, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1973)
In this revision 17 westpalaearctic species are considered, among them four new species for science: T. roubali spec. nov. from the Caucasus, T. longicornis spec. nov. from eastern Europa and from the Caucasus, T. candioticus spec. nov. from Crete and T. paravilis spec. nov. from the Alps. 54 figures facilitate together with a key the determination of the species. The following criteria are discussed for each species: Synonymy, taxonomic problems, biology and geographical distribution. Nomenclatural Actscandioticus Dieckmann, 1973 (Thamiocolus), spec. n.longicornis Dieckmann, 1973 (Thamiocolus), spec. n.paravilis Dieckmann, 1973 (Thamiocolus), spec. n.roubali Dieckmann, 1973 (Thamiocolus), spec. n.